Synthesis of Gallic-Acid-1-Phenyl-1H-[1,2,3]Triazol-4-yl Methyl Esters as Effective Antioxidants - Lone, Shabir H.; Rehman, Shakeel U; Bhat, Khursheed A. (Drug Research, 2017)
Using a click chemistry approach, a series of gallic-acid-1-phenyl-1H-[1,2,3]triazol-4-ylmethyl esters was synthesized to develop more effective antioxidants. The results of DPPH screening indicate that few of the synthesized analogs display better antioxidant effect compared to the standards. Among all, compounds, 9 and 20 displayed highest DPPH radical scavenging effect with IC50 values as low as 6.4±0.2 and 7.9±0.4 µM respectively, compared to the standard ascorbic acid (IC50=12±0.8 µM) and gallic acid (IC50=9.0±0.6 µM). Compound 10 also displayed a potent antioxidant effect with IC50 of 10.80±0.4 µM. This study provides an important aspect with regard to the use of these gallic-acid based synthetic antioxidants in food industry as dietary supplements.
Keywords: gallic acid; ascorbic acid; triazoles; antioxidants; food-industry